Asymmetric Price Movements and Borrowing Constraints: A Rational Expectations Equilibrium Model of Crises, Contagion, and Confusion - YUAN, KATHY (Journal of Finance, 2005)
ABSTRACT This study proposes a rational expectations equilibrium model of crises and contagion in an economy with information asymmetry and borrowing constraints. Consistent with empirical observations, the model finds: (1) Crises can be caused by small shocks to fundamentals; (2) market return distributions are asymmetric; and (3) correlations among asset returns tend to increase during crashes. The model also predicts: (1) Crises and contagion are likely to occur after small shocks in the intermediate price region; (2) the skewness of asset price distributions increases with information asymmetry and borrowing constraints; and (3) crises can spread through investor borrowing constraints.